2009
DOI: 10.1002/mrd.21118
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in early development

Abstract: SUMMARYDevelopment from separate parental germ cells through fertilization and proceeding to a fully functioning adult animal occurs through an intricate program of transcriptional and chromatin changes. Epigenetic alterations such as DNA methylation are an important part of this process. This review looks at the role of DNA methylation in early embryonic development, as well as how this epigenetic mark affects stem cell differentiation and tissue-specific gene expression in somatic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 86 publications
(108 reference statements)
1
89
0
4
Order By: Relevance
“…2D), but at 1 week the cases of ICF (immunodeficiency, centromeric instability and facial anomalies) syndrome, a rare autosomal recessive disease. 6,7 Marked hypomethylation and decondensation of pericentromeric heterochromatin on specific chromosomes have been reported in adult patients with ICF syndrome, 2,6,7 suggesting that Dnmt3b plays a critical role in DNA methylation and genomic stability in adults as well as in embryos.…”
Section: Diurnal Variations Inmentioning
confidence: 99%
See 2 more Smart Citations
“…2D), but at 1 week the cases of ICF (immunodeficiency, centromeric instability and facial anomalies) syndrome, a rare autosomal recessive disease. 6,7 Marked hypomethylation and decondensation of pericentromeric heterochromatin on specific chromosomes have been reported in adult patients with ICF syndrome, 2,6,7 suggesting that Dnmt3b plays a critical role in DNA methylation and genomic stability in adults as well as in embryos.…”
Section: Diurnal Variations Inmentioning
confidence: 99%
“…To investigate the mechanism, we (1) compared the Dnmt3b transcription pattern to the transcription patterns of circadian pacemaker genes, (2) conducted an experiment to analyze is intended to separate the feeding cycle from the light/dark cycle, should lead to a phase-shift in the Dnmt3b mRNA expression pattern. We therefore compared Dnmt3b mRNA expressions at ZT 0, 4, 8, 12 and 16 in an ad-lib fed group and SF group.…”
Section: Diurnal Variations Inmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is one of the most important mechanisms of mammalian epigenetics and regulates cell differentiation as well as individual development by affecting the stability of the chromosome structure, the selectivity of gene expression, and DNA replication, recombination and repair. 12,13 Finally, we also observed increased expressions of parathyroid hormone, cyclin A1-interacting protein 1 and meiosis-expressed gene-1-like genes, suggesting the disease complexity of DCS.…”
Section: Discussionmentioning
confidence: 59%
“…Epigenetic programing predetermines the developmental program and provides necessary direction for the multitude of changes that are required to proceed from a fertilized oocyte to a fully developed adult animal (1). It has been suggested that epigenetic changes are associated with development and differentiation.…”
Section: Introductionmentioning
confidence: 99%